Canals and Communities Small-Scale Irrigation Systems - Mabry, Jonathan B. (University of Arizona Press, 1996)
From the mountains of South America to the deserts of northern Africa to the islands of south Asia, people have devised myriad ways of moving water to sustain their communities and nourish their crops. Many of these irrigation methods have been used over long periods of time and continue to function in diverse ecological and sociopolitical contexts. This book presents case studies and comparative essays about local institutions for managing water resources. Drawn from around the globe, the cases clearly demonstrate that "indigenous" irrigation is often more sustainable, cost-effective, and flexible than has been generally believed. The contributors discuss a wide range of environments, cultural traditions, and historical contexts in which such systems operate, maintaining a common focus on incentives for cooperation, operational rules, collective-choice arrangements, principles of allocation, and conflict-resolution mechanisms. Canals and Communities can serve as a sourcebook for social scientists and development planners investigating the cultural ecology of irrigated agriculture, the ethnology of cooperative social formations, the politics of collective-resource institutions, and the sociology of rural development. The book also provides examples and generalizations about the cross-cultural characteristics of sustainable water resource management and intensive agriculture. Aside from its theoretical contributions to human ecology and anthropology, the book is of practical importance to development studies. The cases it presents make a convincing argument for perpetuating small-scale irrigation systems as part of the world's repertoire of irrigation knowledge and resources. CONTENTS Introduction The Ethnology of Irrigation: Cross-Cultural Characteristics of Local Water Management, Jonathan B. Mabry Patterns of Cooperation and Conflict in Local Irrigation 1. La Gente es Muy Perra: Conflict and Cooperation over Irrigation Water in Cucurpe, Sonora, Mexico, Thomas E. Sheridan 2. Dhasheeg Agriculture in the Jubba Valley of Somalia, Catherine Besteman 3. The Dry and the Drier: Cooperation and Conflict in Moroccan Irrigation, John R. Welch 4. The Political Ecology of Irrigation in an Andean Peasant Community, Paul H. Gelles Methods and Models for Analyzing Local Irrigation 5. Rapid Rural Appraisal of Arid Land Irrigation: A Moroccan Example, John R. Welch, Jonathan B. Mabry, and Hsain Ilahiane 6. Simulation Modelling of Balinese Irrigation, J. Stephen Lansing 7. Institutional Innovation in Small-Scale Irrigation Networks: A Cape Verdean Case, Mark W. Langworthy and Timothy J. Finan Development Lessons from Local Irrigation 8. Qanats and Rural Societies: Sustainable Agriculture and Irrigation Cultures in Contemporary Iran, Michael E. Bonine 9. The Utility of Tradition in Sri Lankan Bureaucratic Irrigation: The Case of the Kirindi Oya Project, Pamela Stanbury 10. The Relevance of Indigenous Irrigation: A Comparative Analysis of Sustainability, Jonathan B. Mabry and David A. Cleveland Conclusion The Hydraulics of History: Evolutionary Trajectories of Local and Centralized Irrigation, Jonathan B. Mabry